The Crises of Imperialism and the Prospect of Socialism - Lauesen, Torkil (Revista de Estudios Globales. Análisis Histórico y Cambio Social, 2024)
In this article, I take the global and long-term perspective on imperialism, from the rise of colonialism and capitalism through its different stages. I do it because it gives a sense of direction of how the world-system will move in the current ecological, economic, and political endgame of capitalism. I use the lens of world-system analysis and dependency theory in my inquiry, to show its relevance in the twenty-one-century. Finally, I discuss the possibilities for a transformation towards a socialist mode of production as an outcome of the current crises.